The effect of occupational safety and health programmes on employee safety performance at manufacturing company - Loganthiran, Taigharaja (2024)
The manufacturing sector is one of the most hazardous industries on a global scale, with a high incidence of occupational accidents and injuries. This investigation investigates the correlation between employee safety performance and occupational safety and health (OSH) programs in a manufacturing organisation. The objectives consist of the identification of critical OSH programs, the evaluation of employee safety performance levels, and the examination of the correlation between these programs and safety outcomes. Structured questionnaires were distributed to 52 local and foreign employees of a manufacturing company in Rawang, Selangor, in order to capture data using a quantitative research approach. SPSS was employed to conduct descriptive and correlation analyses.The findings emphasise that Personal Protective Equipment (PPE) was the most highly ranked OSH program, with Health and Safety Policies and Health and Safety Inspections following closely behind. This suggests that PPE plays a critical role in improving workplace safety. Employees exhibited exceptional safety performance, as evidenced by the SPI values of Safety Training and Participation, Incident Reporting, and Housekeeping, which exceeded 99%, thereby qualifying them as "Extremely Safe." The Spearman's rho correlation demonstrated a moderate positive relationship (r = 0.359, p = 0.009) between safety performance and OSH programs, thereby verifying the efficacy of these initiatives in enhancing employee safety outcomes.The study concludes that well-structured OSH programs have a substantial impact on safety performance, thereby promoting a secure work environment and reducing workplace incidents. The cross-sectional design and the dependence on self-reported data were recognised as limitations. Some suggestions include undertaking longitudinal studies to assess the long-term effects and increasing employee engagement through programs that are not as high on the priority list, such as Occupational Health Surveillance. These discoveries underscore the importance of ongoing investments in occupational safety and health (OSH) programs to foster a culture of safety and guarantee the well-being of employees in the manufacturing sector.